2018
DOI: 10.1002/psc.3138
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid influences the protease activity and posttranslation modifications of the secreted peptides in the moss Physcomitrella patens

Abstract: Plant secretome comprises dozens of secreted proteins. However, little is known about the composition of the whole secreted peptide pools and the proteases responsible for the generation of the peptide pools. The majority of studies focus on target detection and characterization of specific plant peptide hormones. In this study, we performed a comprehensive analysis of the whole extracellular peptidome, using moss Physcomitrella patens as a model. Hundreds of modified and unmodified endogenous peptides that or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 71 publications
0
25
0
Order By: Relevance
“…With the rapid advance of nano liquid chromatography in tandem with ESI-MS/MS (LC-ESI/MS/MS), peptidomics can start to be used to identify multiple peptides in biological samples, without the need to digest the proteins and characterize the resulting peptides [76][77][78]. InPeps were further sequenced directly from the low molecular weight fraction of cells and/or tissues homogenates using liquid-chromatography in tandem with mass spectrometry (LC-MS/MS), without the need of the substrate capture assay [38,[79][80][81][82][83][84]. To date, multiple research groups have identified InPeps in different human cell lines such as HEK293, MCF7 and SH-SY5Y [85], human tissues [86,87], rodents [76][77][78][88][89][90], zebrafish [91], yeast [81], and plants [82,83], even without using the "substrate capture assay" [38,79,90].…”
Section: Seminal Experiments Evidencing That Intracellular Peptides (Inpeps) Generated By Proteasome Activity Were Naturally Present In Cmentioning
confidence: 99%
“…With the rapid advance of nano liquid chromatography in tandem with ESI-MS/MS (LC-ESI/MS/MS), peptidomics can start to be used to identify multiple peptides in biological samples, without the need to digest the proteins and characterize the resulting peptides [76][77][78]. InPeps were further sequenced directly from the low molecular weight fraction of cells and/or tissues homogenates using liquid-chromatography in tandem with mass spectrometry (LC-MS/MS), without the need of the substrate capture assay [38,[79][80][81][82][83][84]. To date, multiple research groups have identified InPeps in different human cell lines such as HEK293, MCF7 and SH-SY5Y [85], human tissues [86,87], rodents [76][77][78][88][89][90], zebrafish [91], yeast [81], and plants [82,83], even without using the "substrate capture assay" [38,79,90].…”
Section: Seminal Experiments Evidencing That Intracellular Peptides (Inpeps) Generated By Proteasome Activity Were Naturally Present In Cmentioning
confidence: 99%
“…However, the rapid development of modern mass-spectrometry analysis coupled with the explosive growth of genetic data banks has led to the considerable expansion of the list of characterized native peptidomes. Tens of thousands of peptides that significantly differ in their origin, function and properties have been identified in the tissue and biological fluids of multiple organisms [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Even though the peptidomes of prokaryotic and eukaryotic cells comprise thousands of peptides, the majority of them are generated during protein degradation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we summarize our knowledge about the generation of different types of peptides, their precursors and biological function. In addition, we analyzed selected peptidome datasets ( Table 1 ) from plants [ 15 , 16 , 62 ], bacteria [ 63 ], humans [ 12 , 64 ] and yeast [ 65 ] to identify some common trends in their composition and physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Filippova et al showed that a substantial portion (about 10%) of the moss Physcomitrella patens secretome peptides contains modifications, for example, hydroxylated proline. The authors of this study also suggest that such peptides might be generated inside the cell and then released via different pathways into the extracellular space or might be cleaved out from their precursors in the extracellular space [24]. However, the role of intracellular and extracellular peptide pools in plant immune response is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The most abundant types of proteases shaping the extracellular pool of endogenous peptides in the moss Physcomitrella patens are serine-type (subtilisin-like) proteases, mealloproteases, and aspartic-type proteases. Treatment with salicylic acid leads to an increase in the number of endogenous peptides potentially cleaved by serine-type and aspartic-type proteases [24]. Evidence is emerging about the important role of the plant ubiquitin—proteasome system (UPS) in defense and stress hormone turnover regulation [33,34].…”
Section: Introductionmentioning
confidence: 99%